Design of Dual-Focal-Plane AR-HUD Optical System Based on a Single Picture Generation Unit and Two Freeform Mirrors - Chengxiang Fan; Lingbao Kong; Bo Yang; Xinjun Wan (Photonics, 2023)
Augmented reality heads-up displays (AR-HUDs) have a much richer display than traditional heads-up displays. An ideal AR-HUD requires two or more focal planes to display basic and interactive driving information to the car driver separately. We present an off-axis reflective optical structure for dual-focal-plane displays using a single projection-type picture generation unit (PGU) and two freeform mirrors. The dual-focal-plane AR-HUD system designed in this paper can simultaneously generate high-quality far-field image (13° × 4°, 10 m) and near-field images (13° × 1.4°, 3.5 m) in a 130 mm × 60 mm eyebox. A fully automated analysis program is written to analyze the modulation transfer function (MTF) and distortion values of the optical system over the entire eyebox range. The analysis results show that the maximum distortion values of the far-field image and near-field image in the eyebox range are 3.15% and 3.58%, respectively. The MTF was greater than 0.3 at 7.2 lp/mm for both near-field images and far-field images. We also designed a projection lens for the projection-type PGU used in this system. The projection lens uses three plane mirrors to fold the image plane of the projection system into different positions to serve as the image source for the AR-HUD. This research provides a new solution for realizing the dual-focal-plane AR-HUD, which not only satisfies the need for simultaneous display of near-field basic information and far-field interactive information, but also has a larger display screen.